Maternal and neonatal outcomes among puerperal women screened for SARS-CoV-2 at Hospital San Juan de Lurigancho, April to September 2020 - Barrios-Cárdernas, Pascual (2021)
Introduction: The SARS-CoV2 virus could cause adverse maternal and neonatal outcomes due to the changes inherent in pregnancy and its investigation is necessary. Objective: To compare the maternal and neonatal results among the puerperal women screened for SARS-CoV-2 at the San Juan de Lurigancho Hospital, April to September 2020. Materials and Methods: A quantitative study with an analytical, retrospective and cross-sectional design, included a sample Of 377 puerperal women screened for SARS-CoV-2, puerperal women with incomplete medical records were excluded. The technique was the documentary review, using a validated data collection sheet, it had ethical approval; Descriptive statistics and the Chi square test were used for statistical analysis. Results: 26.5% had a reactive result to SARS-CoV-2. 60.2% had vaginal delivery, 78% did not have prenatal care (p = 0.005), only 5% had a hypertensive disorder, 1.1% had gestational diabetes (p = 0.042), 63.1% had anemia and dysfunctional labor was 4.2% (p = 0.005). Among the neonatal outcomes, macrosomia was present in 8% (p = 0.015). Conclusions: Attendance at prenatal control, gestational diabetes, and dysfunctional labor had a significant difference between reactive and non-reactive patients to SARS-CoV-2, while in neonatal outcomes this occurred with neonatal weight.